(untitled) (International Journal of Food and Nutritional Sciences, 2022)
India’s spices are well-known both within the country and internationally for their flavor and aroma. It is well acknowledged that India is among the leading producers, consumers, and exporters of spices worldwide. Data from secondary sources were used in the study. The level of export competitiveness and market competitiveness for the primary spices, which include cumin, black leaf, turmeric, and chilli, was measured by employing a constant pricing analysis that was performed. It was discovered that the global market competitiveness of chili, turmeric, and coriander is quite high.